2019
DOI: 10.1007/s00127-019-01758-y
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic inequalities in the incidence of diagnosis of severe mental illness in England: a systematic review and new meta-analyses for non-affective and affective psychoses

Abstract: Purpose Although excess risks particularly for a diagnosis of schizophrenia have been identified for ethnic minority people in England and other contexts, we sought to identify and synthesise up-to-date evidence (2018) for affective in addition to non-affective psychoses by specific ethnic groups in England. Methods Systematic review and meta-analysis of ethnic differences in diagnosed incidence of psychoses in England, searching nine databases for reviews (citing relevant studies up to 2009) and an updated se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 77 publications
(144 reference statements)
7
60
0
Order By: Relevance
“…A recent meta‐analysis gave a pooled risk ratio of incident diagnosed schizophrenia in the Black Caribbean population of 5.1 (95% CI 4.2–6.2), an even higher risk for Black African people (6.0, 95% CI 3.5–10.2) and a raised risk for South Asian and White minority groups (respectively 2.3, 95% CI 1.6–3.3 and 2.5, 95% CI 1.7–3.6) (Halvorsrud et al . ). Similar findings have been reported in other developed countries (Bresnahan et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent meta‐analysis gave a pooled risk ratio of incident diagnosed schizophrenia in the Black Caribbean population of 5.1 (95% CI 4.2–6.2), an even higher risk for Black African people (6.0, 95% CI 3.5–10.2) and a raised risk for South Asian and White minority groups (respectively 2.3, 95% CI 1.6–3.3 and 2.5, 95% CI 1.7–3.6) (Halvorsrud et al . ). Similar findings have been reported in other developed countries (Bresnahan et al .…”
Section: Introductionmentioning
confidence: 97%
“…Importantly, the UK findings have been reported consistently for more than 60 years and appear to be persistent over time and across generations (Bagley , Cochrane and Bal , Halvorsrud et al . , Harrison et al . , Kiev , King et al .…”
Section: Introductionmentioning
confidence: 99%
“…• Black men are more likely to be diagnosed with severe mental illnesses such as schizophrenia and other psychotic disorders. [4][5][6] More conservative studies have demonstrated that Black men are at least three times more likely to receive a diagnosis of psychotic illness compared to White men. 5 While this disparity is well documented in the literature, underlying mechanisms continue to be poorly defined and understood.…”
Section: The Inequalities Faced By Black Men Accessing Mental Health mentioning
confidence: 99%
“…• Black men are significantly less likely to have GP involvement in their diagnostic journey. 4,5 As primary care doctors, our role is to oversee, manage, and guide the patient towards appropriate specialist care. When this is absent from their care journey, we are failing to properly safeguard the needs of our patient in a holistic manner.…”
Section: The Inequalities Faced By Black Men Accessing Mental Health mentioning
confidence: 99%
“…A recent systematic review and metaanalysis provides more information on ethnic inequalities in the incidence of diagnosis of severe mental illness (1) People of ethnic minorities have been found to be at increased risk of receiving a diagnosis of schizophrenia. Halvorsrud et.…”
mentioning
confidence: 99%